Modela nastanka ligninskega polimera - Gričar, Jožica (Les (Ljubljana), 2005)
In paper, two models of formation of lignin macromolecule are described. Random coupling model suggests lignin formation process through coupling of monomer radicals to growing lignin polymer in a near-random fashion. According to the dirigent protein model, process of lignin polymerization is fully controlled by specific dirigent proteins that direct formation of individual bonds. Critical judgements and scientific opinions of both models are given.
Keywords: lignin; sinteza; biosinteza; modeli